1985
DOI: 10.1111/j.1471-4159.1985.tb10530.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to Benzodiazepines

Abstract: Four hybridoma lines secreting monoclonal antibodies to benzodiazepines were produced after BALB/c mice were immunized with a benzodiazepine-bovine serum albumin conjugate. The monoclonal antibodies were purified from ascites fluids, and their binding affinities for benzodiazepines and other benzodiazepine receptor ligands were determined. These antibodies have very high binding affinities for diazepam, flunitrazepam, Ro5-4864, Ro5-3453, Ro11-6896, and Ro5-3438 (the KD values are in the 10(-9) M range). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In these studies we used an anti-benzodiazepine monoclonal antibody (mAb) (1,2). This finding was supported by immunocytochemistry and immunoblotting experiments as well as by the purification by immunoaffinity chromatography of a rat brain substance that inhibited [3H]flunitrazepam binding to the neuronal-type benzodiazepine receptor (3,4).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…In these studies we used an anti-benzodiazepine monoclonal antibody (mAb) (1,2). This finding was supported by immunocytochemistry and immunoblotting experiments as well as by the purification by immunoaffinity chromatography of a rat brain substance that inhibited [3H]flunitrazepam binding to the neuronal-type benzodiazepine receptor (3,4).…”
mentioning
confidence: 95%
“…Useful spectra appeared as the probe was heated to 100°C, about the same temperature as required by authentic N-desmethyldiazepam. (2). The blockage of immunoreactivity by Ro 5-4864 and diazepam is due to the high affinities of these benzodiazepines for mAb 21-7F9 and does not necessarily reflect the specificity of the endogenous substance for the "peripheral" or '"central" type of benzodiazepine receptor.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The production of the hybridomas and the comparative study of the BZD binding properties of this and other antibodies will be reported elsewhere (38). The hybridomas secreting mAbs to BZD were identified by assaying the conditioned culture media in three ways: (i) binding of 3H-labeled flunitrazepam (FNZ) tp the mAbs, (ii) antibody competition with tie [3H]FNZ binding to the brain membrane BZDR, and (iii) antibody binding to the 3-hemisuccinyloxyclonazepam conjugate with keyhole limpet hemocyanin (BZD-KLH) in a standard ELISA assay.…”
Section: Methodsmentioning
confidence: 99%
“…This raises the possibility that such compounds could act as endogenous agonists (De Blas et al, 1985). However, there is no evidence that such compounds are synthesized in vivo (Izquierdo and Medina, 1993).…”
Section: Are There Natural Ligands For the Benzodiazepine Receptor Inmentioning
confidence: 97%